Santri and Santriwati's Understanding of Gender Stereotypes in the Environment of the Ngegong Tahfidz Qur'an Islamic Boarding School - Viandari, Nuraini Okta; Hadi, Nur (CV Bumi Spasial, 2025)
Gender-related issues remain deeply embedded within societal structures, manifesting across various domains of public and private life. Among the most persistent of these issues is the perpetuation of gender stereotypes socially constructed assumptions about roles and characteristics assigned to individuals based on gender. This study aims to explore how gender stereotypes are understood by male and female students (santri and santriwati) within a religious education setting, specifically at the Tahfidz Mamba’u Syafa’atil Qur’an Islamic Boarding School in Blitar, Indonesia. Employing a qualitative descriptive methodology, data were collected through purposive sampling, in-depth interviews, observation, and documentation. The analysis was guided by postmodern feminist theories, particularly those of Judith Butler and Julia Kristeva, to examine how gender perceptions are shaped through religious instruction and social interaction in the pesantren environment. Findings indicate that students internalize gender roles through sustained exposure to religious teachings and community norms, leading to differentiated understandings of male and female roles. These roles are often justified through perceived innate differences in physical and emotional attributes. The study identifies four primary implications of these stereotypes within the boarding school context: spatial mobility restrictions, gendered division of roles and responsibilities, character formation aligned with traditional gender norms, and entrenched perceptions that hinder gender equality. This research contributes to the discourse on gender in religious educational institutions by highlighting the complex interplay between doctrine, tradition, and evolving gender consciousness among youth.